The Embryotoxic Effects of in Ovo Administered Sunset Yellow FCF in Chick Embryos - Colakoglu, Fatma (Vet Sci, 2021)
Sunset yellow (SY) at prescribed concentrations has been approved by regulatory authorities in several countries as an additive dye in the food, beverage, cosmetic, and pharmaceutical industries. However, there are some reports that it may cause several health problems. The aim of this study is to evaluate embryotoxic effects of SY on liver and kidney in chick embryos. Babcock white Leghorn eggs were randomly divided into four groups. Non-treated eggs served as control group. The eggs in groups SY(200), SY(1000), and SY(2000) were treated with a single injection of 200, 1000, and 2000 ng SY into the air sac just before incubation. The developmental stages of embryos were determined on the 10th, 13th, 16th, and 21st days of incubation. Samples of the liver and kidney were taken and routine histological procedures were performed. The highest relative embryo weight was seen in all SY treated groups on the 16th day of incubation. Necrosis of some hepatocytes and cytoplasmic degenerations were observed in all SY groups in the liver. There were degenerated or destructed renal cortex structures and necrosis in the kidney. The cell’s nuclear areas and diameters of renal cortex structures were different in all SY groups compared to the control group (p < 0.05). It was concluded that in ovo administered SY has many unfavorable effects on liver and kidney in chick embryos. The results obtained in this study suggest that it may be advisable to re-assess safety levels of SY in many industries.